2020
DOI: 10.1177/1724600820980739
|View full text |Cite
|
Sign up to set email alerts
|

Difference of copy number variation in blood of patients with lung cancer

Abstract: Background: Lung cancer is the leading cause of cancer-related deaths worldwide. Copy number variation (CNV) in several genetic regions correlate with cancer susceptibility. Hence, this study evaluated the association between CNV and non-small cell lung cancer (NSCLC) in the peripheral blood. Methods: Blood samples of 150 patients with NSCLC and 150 normal controls were obtained from a bioresource center (Seoul, Korea). Through an epigenome-wide analysis using the MethylationEPIC BeadChip method, we extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…In our cohort, cases presented with overall more duplications, but not more deletions, as compared to controls (burden analysis, based on all CNVs with at most 10% frequency, 823 called duplications in 297 cases versus 626 called duplications in 277 controls, p = 0.01, based on 10,000 permutations, see Figure 2 ). This range of CNV counts is in line with previous studies using similar technology and sample sizes [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 90%
“…In our cohort, cases presented with overall more duplications, but not more deletions, as compared to controls (burden analysis, based on all CNVs with at most 10% frequency, 823 called duplications in 297 cases versus 626 called duplications in 277 controls, p = 0.01, based on 10,000 permutations, see Figure 2 ). This range of CNV counts is in line with previous studies using similar technology and sample sizes [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 90%
“…In this study, we found that CNV including CCND1, FGF3/4/19 genes in male, smoking and LUSC cases was significantly enhanced than female, no-smoking and LUAD, respectively. Consistently, Heo and the colleagues have reported significant associations between CNV and smoking, such as acyl-CoA thioesterase 1 (ACOT1), N-terminal acetyltransferase F (NAA60), gasdermin-D (GSDMD) and HLA-DPA1 genes [ 18 ].…”
Section: Discussionmentioning
confidence: 87%
“…As a result, 47 PRGs and 33 ICDGs were identi ed 14,16 . Gene mutations and copy number variations reportedly promote the progression of cancer [17][18][19] . Therefore, the gene mutation frequency and copy number variation frequency of PRGs and ICDGs in HNSCC were investigated in the present study.…”
Section: Comparison Of the Genome And Transcriptome Alterations In Hnsccmentioning
confidence: 99%